Mood states and well-being of spouses of fibromyalgia patients: a systematic review and meta-analysis - Treister-Goltzman, Yulia; Peleg, Roni (Frontiers in Psychology, 2024)
Background We carried out a systematic review of the medical literature on potential effects of caregiving on the health and well being of spouses of Fibromyalgia (FM) patients and pooled the results in a meta-analysis. Methods The review is comprised of original studies that examined the mood states and well-being of husbands/wives, or long-term intimate partners, of FM patients. The authors searched the PubMed, Scopus, APA PsycNet and Web of Science databases using the key words “fibromyalgia and spouses,” “fibromyalgia and partners,” and “fibromyalgia and husbands.” Of 570 papers that were initially identified using the search words, 18 papers were considered eligible. We used the Joanna Briggs Institute Critical Appraisal Checklist (JBICAC) and Critical Appraisal Skills Program (CASP) tools to assess the risk of bias in the analytical cross-sectional and qualitative studies, respectively. Results The overall score in mood states was significantly higher among spouses of FM patients than among spouses of individuals without FM (SMD [95% CI] = 0.52 [0.30; 0.74]). The strongest evidence was found for depression, SMD [95% CI] = 0.68 [0.33; 1.03]. The overall standardized score of quality of life was significantly lower among spouses of FM patients, SMD [95% CI] = −0.59 [−0.79; −0.38], with significant differences in physical function and role, emotional role, and mental health subscales. Limitation Limitation of this review is the scant number of studies that addressed several health domains, which made it impossible to carry out meta-analyses in these domains. Conclusion Spouses of FM patients show the emotional and physical consequences of caregiving, and impaired quality of life. Addressing these problems can prevent deterioration of their health and improve their quality of life.